2021
DOI: 10.1089/tmj.2020.0270
|View full text |Cite
|
Sign up to set email alerts
|

Sustaining Gains in Diabetic Eye Screening: Outcomes from a Stakeholder-Based Implementation Program for Teleophthalmology in Primary Care

Abstract: Background: Teleophthalmology is a validated method for diabetic eye screening that is underutilized in U.S. primary care clinics. Even when made available to patients, its long-term effectiveness for increasing screening rates is often limited. Introduction: We hypothesized that a stakeholder-based implementation program could increase teleophthalmology use and sustain improvements in diabetic eye screening. Materials and Methods: We used the NIATx Model to test a stakeholder-based teleophthalmology implement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…In our prior work, we found that tailored implementation of telemedicinebased screening using health system-level interventions, such as primary care workflow changes and patient recall systems, led to significant and sustained increases in screening rates in a rural health system. 18 Targeted use of health system-level interventions in diabetes populations with lower screening rates, including rural and urban underserved populations, Black and Latinx communities, as well as younger populations, 8 10 33 could be highly effective in increasing screening rates.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In our prior work, we found that tailored implementation of telemedicinebased screening using health system-level interventions, such as primary care workflow changes and patient recall systems, led to significant and sustained increases in screening rates in a rural health system. 18 Targeted use of health system-level interventions in diabetes populations with lower screening rates, including rural and urban underserved populations, Black and Latinx communities, as well as younger populations, 8 10 33 could be highly effective in increasing screening rates.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review by Zhang et al 32 identified five randomized controlled trials in which health system-level interventions, including telemedicine, significantly increased diabetic retinopathy screening, with relative risks ranging from 1.12 (95% CI 1.03 to 1.22) to 5.56 (95% CI 2.19 to 14.10). In our prior work, we found that tailored implementation of telemedicine-based screening using health system-level interventions, such as primary care workflow changes and patient recall systems, led to significant and sustained increases in screening rates in a rural health system 18. Targeted use of health system-level interventions in diabetes populations with lower screening rates, including rural and urban underserved populations, Black and Latinx communities, as well as younger populations,8 10 33 could be highly effective in increasing screening rates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specific outcome measures have included changes in the number of patients screened, the number who followed up to eye care, demographics, modeled costs, and patient satisfaction [ 5 , 6 , 8 - 18 , 21 - 25 ]. A recent study focused on implementing teleophthalmology explored how rural primary clinics in Wisconsin viewed the implementation of teleophthalmology using qualitative analysis and an implementation science framework [ 26 ]. Another study focused on the implementation of teleophthalmology across federally qualified health centers in Kentucky using implementation science metrics [ 27 ].…”
Section: Introductionmentioning
confidence: 99%